Analisis Strategi Pemasaran Bakso Barupi ( Bakso Rusa Sapi ) Di Desa Burni Bius Kecamatan Silih Nara Kabupaten Aceh Tengah - fitri, ilma (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) UGP, 2025)
Meatball traders are one of the businesses engaged in fast food processing. This meatball business has been around for a long time and has developed in rural areas in several sub-districts in Central Aceh Regency, one of which is in Silih Nara District. This meatball business has been able to survive since 2019 until now. This Barupi meatball stall (beef deer meatballs) is in great demand by local residents, even its customers have spread to Takengon City, even its customers come from outside Bener Meriah Regency, Bireuen and others. The purpose of this study is to